Space in the ancient novel - Paschalis, Michael; Frangoulidis, Stavros A. (Ancient narrative. Supplementum., 2002)
This special issue of Ancient Narrative Supplementum 1, entitled 'Space in the Ancient Novel', brings together a collection of revised papers, originally presented at the International conference under the same title organized by the Department of Philology (Division of Classics) of the University of Crete and held in Rethymnon, on May 14-15, 2001. This conference inaugurated what is hoped to become a new series of biennial International meetings on the Ancient Novel (RICAN, Rethymnon International Conferences on the Ancient Novel) which aspires to continue the reputable tradition of the Groni.